2013
DOI: 10.1161/hypertensionaha.113.01549
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in the Transition From Masked to Sustained Hypertension in Healthy Youths

Abstract: C linicians who care for children and adolescents are now facing changes in hypertension, which include new methods for measuring blood pressure (BP) and assessing associated cardiovascular risk factors and target organ damage. Although conventional BP should be used as a reference method for measuring BP and diagnosing hypertension, ambulatory BP monitoring (ABPM) has been introduced into the pediatric population. According to European and American recommendations, ABPM is now increasingly recognized as being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 36 publications
0
29
0
2
Order By: Relevance
“…In a general population of adolescents, 10-19 years, the rate of progression from normotension to HTN was 0.4/100 subjects/year, and among those who had high-normal BP it was 1.1/100 subjects/year (42). In another study on normotensive children with a mean follow-up of 35 months, the incidence of sustained HTN was 0.6/100 subjects/year (43). In the same study, masked hypertensive subjects had an incidence of sustained HTN of 7/100 subjects/year, the risk being higher in boys than in girls (43).…”
Section: Incidencementioning
confidence: 94%
See 3 more Smart Citations
“…In a general population of adolescents, 10-19 years, the rate of progression from normotension to HTN was 0.4/100 subjects/year, and among those who had high-normal BP it was 1.1/100 subjects/year (42). In another study on normotensive children with a mean follow-up of 35 months, the incidence of sustained HTN was 0.6/100 subjects/year (43). In the same study, masked hypertensive subjects had an incidence of sustained HTN of 7/100 subjects/year, the risk being higher in boys than in girls (43).…”
Section: Incidencementioning
confidence: 94%
“…In another study on normotensive children with a mean follow-up of 35 months, the incidence of sustained HTN was 0.6/100 subjects/year (43). In the same study, masked hypertensive subjects had an incidence of sustained HTN of 7/100 subjects/year, the risk being higher in boys than in girls (43). The incidence in adolescents with T2D was estimated as 4/100 subjects/year (44).…”
Section: Incidencementioning
confidence: 96%
See 2 more Smart Citations
“…73 Further, Lurbe and colleagues, in a cohort of 272 subjects aged 6-18 years showed that subjects with MHT (n=39) presented a higher risk of sustained hypertension during time, and this risk was higher in male patients. 74 Although clinic BP is in the normal range in subjects with MHT, optimal values (<120/80 mmHg) are related to a lower prevalence of this alteration with a lower presence of TOD 75 and also with a lower incidence of MHT during a long follow-up period. 76 However, this cut-off value lead to an high false-positive rate.…”
Section: Clinical Consequencesmentioning
confidence: 98%